Karakteristik biodiesel dari minyak jelantah menggunakan katalis abu gosok dengan variasi penambahan metanol - Yelmira Zalfiatri; Fajar Restuhadi; Rizky Zulhardi (Universitas Jambi, Fakultas Sains dan Teknologi, Program Studi Kimia, 2019)
Biodiesel is the reaction esterification and transesterification between oil and alcohol. Biodiesel raw materials in the form of vegetable oil, one of which is Waste Cooking Oil (WCO). This study aims to obtain the addition of the best methanol in the manufacture of biodiesel from cooking oil. The research method used Randomized Complete Design (RAL) with M1 treatment (methanol 65 ml), M2 (methanol 75 ml), M3 (methanol 85 ml) and M4 (95 ml methanol). The best result was obtained with addition of 95 ml of methanol (M4) with 0.42 mg KOH / g, total glycerol 0,08%, flash point 227 ° C, saponification number 123,46 mg KOH / g and methyl ester 99 , 4%.